Symmetry-Breaking Charge Separation in a Nanoscale Terrylenediimide Guanine-Quadruplex Assembly - Powers-Riggs, Natalia E; Zuo, Xiaobing; Young, Ryan M; Wasielewski, Michael R (Journal of the American Chemical Society, 2019)
Guanine-quadruplex (G-quadruplex) assemblies provide a useful platform for studying the spatial, structural, and photophysical effects of intermolecular interactions. Coupling a single guanine moiety to terrylenediimide (TDI)a chromophore with a large extended π-surfaceproduces a structure (GTDI) that assembles in plate-like tetramers, with the potential of undergoing tunable π-stacking. At high concentrations (3 × 10–3 M), GTDI self-assembles into a nearly monodisperse G-quadruplex structure of 16 layers, with strong π-overlap between TDI moieties, observed by small- and wide-angle X-ray scattering. Transient absorption spectroscopy reveals that excitation of TDI in the G-quadruplex results in symmetry-breaking charge separation to form ion pairs within the structure, owing to the strong π-overlap enforced by the hydrogen-bonding. These assemblies yield important insights into the interplay of noncovalent interactions in the assembly of ordered chromophoric arrays.